ANALYSIS OF KURIKULUM MERDEKA IN SEKOLAH PENGGERAK - Ali Muckromin; Anam Sutopo; Yulia Maftuhah Hidayati; Choiriyah Widyasari (Universitas Majalengka, 2023)
Education cannot be limited by space and time as Ki Hajar Dewantara said: